Uncertainty, conflict and consent: revisiting the futility debate in neurotrauma - Honeybul, Stephen; Gillett, Grant R.; Ho, Kwok M. (Acta neurochirurgica, 2016)
The concept of futility has been debated for many years, and a precise definition remains elusive. This is not entirely unsurprising given the increasingly complex and evolving nature of modern medicine. Progressively more complex decisions are required when considering increasingly sophisticated diagnostic and therapeutic interventions. Allocating resources appropriately amongst a population whose expectations continue to increase raises a number of ethical issues not least of which are the difficulties encountered when consideration is being given to withholding “life-preserving” treatment. In this discussion we have used decompressive craniectomy for severe traumatic brain injury as a clinical example with which to frame an approach to the concept. We have defined those issues that initially lead us to consider futility and thereafter actually provoke a significant discussion. We contend that these issues are uncertainty, conflict and consent. We then examine recent scientific advances in outcome prediction that may address some of the uncertainty and perhaps help achieve consensus amongst stakeholders. Whilst we do not anticipate that this re-framing of the idea of futility is applicable to all medical situations, the approach to specify patient-centred benefit may assist those making such decisions when patients are incompetent to participate.